Toxic Effects of Copper Nanoparticles on Paramecium bursaria–Chlorella Symbiotic System - Tan, Bingyu; Wang, Yiwen; Gong, Zhiwei; Fan, Xinpeng; Ni, Bing (Frontiers in Microbiology, 2022)
Although many reports have demonstrated that nanoparticles can have a negative effect on aquatic organisms, the toxic effects on symbiotic organisms remain poorly understood. The present study conducts ultrastructure, enzyme activity, and transcriptomics to assess the toxic effects to the Paramecium bursaria–Chlorella symbiotic system from exposure to copper nanoparticles (CuNPs) for 24 h. We found that in both the host and symbiotic algae, CuNP exposure induced high reactive oxygen species level, which leads to oxidative damage and energy metabolism disorder. Moreover, transmission electron micrographs (TEMs) showed that the symbiotic algae in the cytoplasm of P. bursaria were enveloped in the digestive vacuole and digested, and the level of acid phosphatase activity increased significantly within 24 h, which indicated that the stability of the symbiotic system was affected after CuNP exposure. We speculated that the increased energy demand in the host and symbiotic algae resulted from oxidative stress, precipitating the decrease of the photosynthetic products provided to the host, the digestion of the symbiont, and the destruction of the stable symbiotic relationship. The study provides the first insight into the mechanisms of nanoparticles’ toxicity to the symbiotic relationship in the ecosystem, which may help to understand the environmental effects and toxicological mechanisms of nanoparticles.